The Effect of Djenkol (Pithecellobium Lobatum Benth.) Seeds Ethanol Extract on Levels of Blood Glucose, Urea and Creatinine in White Male Rats (Rattus Norvegicus) Sprague Dawley Strain induced Alloxan - Lumban Gaol, Frisca Febe; Susantiningsi, Tiwuk; Kurniawaty, E (Majority, 2014)
Diabetes Mellitus (DM) is a chronic disease that caused by the body’s inability to produce or properly use insulin effectively. The characteristic of DM are polyuria, polydipsia, polyphagia, and the increase of blood glucose. The number of patients with DM in Indonesia in 2000 ranks 4th in the world, amounting to 8.4 million people . Jengkol is a kind of plant that can lower blood sugar levels, but also can cause acute renal failure due to jengkolat acids that contained in djenkol . To diagnose acute renal failure, renal function tests should be done by measuring the levels of urea and creatinine. This study is an experimental study, using the design of the Post Test Only Control Group Design. This study use 25 rats (Rattus norvegicus ) male Sprague Dawley strain that devided being 5 grups. Based on the results of the ANOVA test , the value of p < 0.05 on rat blood glucose levels. Unlike the results of statistical tests performed on the levels of urea and creatinine , resulting p > 0.05. It’s means that the ethanol extract of the djenkol seeds can decrease blood glucose levels , but did not affect to increase the levels of urea and creatinine in male rats Sprague Dawley strain induced alloxan. However, based on the mean creatinine levels, Djenkol seeds ethanol extract at a dose of 1200 mg/kgbb could lead to decrease of renal function with elevated creatinine values were expressed as 0,86 mg/dl. Keywords : Alloxan , creatinine, djenkol, glucose, urea